Tıp Fakültesi Öğrencilerinin Yurt Dışında Çalışmasına Yönelik Tutum Ölçeği. - HARMAN YILDIZ, Güzin; ÖZER, Kubilay (Journal of Selçuk University Social Sciences Vocational School)
Physicians, who are the basic building blocks of health services, and medical faculty students, who are physician candidates, have come to the fore with demands to migrate and work abroad in recent years. Medical students' desire to work abroad has a significant impact on healthcare systems and medical education. This study aimed to measure the attitudes of medical faculty students towards working abroad and to develop a scale. At the same time, the validity and reliability of the scale were tested in this study and are presented through tables and figures under relevant headings. The research was conducted on 4-5-6 students studying at Meram Medical Faculty of Necmettin Erbakan University in Konya. The class was held with the participation of 400 students. A data collection tool was prepared as a result of the literature review regarding the attitudes of physician candidates about working abroad. Questions prepared in the form of 5-point Likert were determined by selecting 50 items from the created item pool. For content validity, it was reduced to 40 items by taking expert opinions and a pilot study was conducted. The structure analysis of the scale with the data obtained was made with Exploratory Factor Analysis (EFA) and it was determined that it explained 66.53% of the total variance. After EFA, the scale was collected into 18 items and 4 subscales. In the light of the data obtained, Confirmatory Factor Analysis (CFA) of the scale was carried out. SPSS and AMOS computer programs were used to analyze the data. The reliability of the scale was tested with Cronbach Alpha Coefficient and was found to be 0.843. As a result of the analyses, the Attitude Scale of Medical Faculty Students Towards Working Abroad was obtained, with 18 items and 4 factors (1. Expectations, 2. Awareness, 3. Severity, 4. Preference and 5 Tendencies).